Impact of farm size on pesticide use: evidence from Chinese rice production - Yuan, Yinghui; Zhu, Xiaowei; Wang, Changyi; Zai, Xueming; Song, Yulan; Amar, Nimra (Frontiers in Sustainable Food Systems, 2025)
IntroductionChina’s position as the world’s largest consumer of chemical pesticides presents a critical challenge to the long-term sustainability of its food production systems. While vital for past food security achievements, the excessive application of these chemicals now degrades agro-ecological health and hinders sustainable agricultural development. Many studies have investigated technological fixes, yet a key structural question remains: how does farm size affect chemical dependency?MethodsThis study employs a 2SLS model and uses farm-level rice data from Jiangsu Province (2004-2017) to analyze the impact of farm size on pesticide costs.Results and discussionWe find a U-shaped relationship between farm size and pesticide use. At the sample mean, a 1% increase in farm size is associated with a 0.089% decrease in pesticide cost per unit of land (mu) and a 0.104% decrease per kilogram of rice. This finding suggests that for the majority of farms, increasing scale is currently aligned with greater pesticide use efficiency. It challenges the notion that small-scale farming is inherently more sustainable, indicating that an optimal scale exists for minimizing chemical dependency. The paper concludes with policy implications for designing pathways toward a more sustainable, low-input food system in China.